Analysis of Spatio Temporal Change of Land Use of Chrysanthemum Farm in Semarang Regency Using Landsat Image 8 OLI - Priyadi Priyadi (Pusat Studi Sistem Informasi dan Pemodelan Mitigasi Tropika, 2018)
Agriculture is a business issue that has long existed and will likely continue to exist throughout the ages. Similarly, on the issue of agricultural land use chrysanthemum that needs to be developed method of analysis using technology approach and computer science. This research intends to analyze and develop effective and efficient methods of chrysanthemum land use. The satellite imagery data covering pre-processing, processing and post processing in this research is mostly done with QGIS software. Satelite image used in this research is LANDSAT 8 OLI and band used are band 6, bang 5, band 2 and band 8. Stages of working this research include image cutting in the research area of all bands and all temporal images involved in research, pansharpening using